(untitled) (Bangladesh Journal of Urology, 2025)
Background: Detrusor overactivity (DO) is a biomarker for overactive bladder (OAB) which is seen in urodynamic study. Urodynamic study is indicated in OAB when occult diagnosis suspected which may alter management, refractory OAB; and potential morbid surgery planned. Urodynamic test is costly, invasive and time consuming. Ultrasonogram (USG) measured bladder wall thickness is the simplest option as it is cheap, available and noninvasive procedure. This study has been designed to find the role of trans-abdominal USG measured urinary bladder wall thickness (BWT) to diagnose urodynamicaly proven detrusor overactivity. Materials and methods: Total 30 refractory OAB patients were included for the study. All study population underwent BWT measurement and urodynamic study. Study population was categorized into Group A and Group B according to presence and absence of DO in urodynamic study. Student t-test and Chi-square test were used to compare continuous and categorical variable respectively. Pearson Correlation test was used to detect the relationship between BWT and age. Sensitivity and specificity of BWT in the diagnosis of DO were measured by ROC curve. Result: Bladder wall thickness was significantly greater in DO group compared to no DO group (p<0.001). But the area under the curve (AUC) was 0.0928 denoting very low diagnostic accuracy of bladder wall thickness for the diagnosis of DO. Conclusion: Higher bladder wall thickness may be a useful method to detect DO. Ultrasound for bladder wall thickness is not standardized for at which point of bladder volume to measure BWT, probe frequency, routes of measurement and site of measurement in urinary bladder. Bladder wall thickness is not an alternate diagnostic tool for DO. Trans-abdominal ultrasound measured BWT canʼt be used as biomarkers for DO in OAB patient. Bangladesh J. Urol. 2024; 27(2): 101-107